INVESTMENTS IN DEVELOPMENT OF SUPPLY CHAINS - E. A. Balchik (Real Economics Publishing House, 2018)
The problems of investment in the development of supply chains are considered. The trends that are characteristic of investment processes in the industry are investigated, and problems of investing in the supply chain are highlighted, namely, the lack of a wellcoordinated partnership between the state and private business, underestimation of projects due to incomplete information about the characteristics of investment projects and underdeveloped investment assessment methodology. The authors confirmed the thesis that the development of investment in innovative solutions for supply chains is ensured by more active participation of stakeholders in the investment process.